2009
DOI: 10.17925/eoh.2009.03.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Anaplastic Lymphoma Kinase Rearrangements in Lymphoma

Abstract: Lymphomas expressing anaplastic lymphoma kinase (ALK) represent two distinct lymphoma entities: ALK-positive T-/null-cell anaplastic large cell lymphoma (ALK + ALCL) and ALK-positive large B-cell lymphoma (ALK + LBCL). In both subtypes, the inappropriate expression of ALK is driven by 2p23/ALK-involving chromosomal translocations found to target several partner genes. These translocations lead to constitutively activated and oncogenic ALK fusions, of which nucleophosmin (NPM1)-ALK associated with t(2;5)(p23;q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Even though the complete PTK domain is involved, the ALK fragment contains the final 513 amino acids, which is shorter in comparison to the fragment involved in most other ALK fusions, containing the final 563 amino acids. 42 Of note, both cases reported by Palacios et al 33 revealed breakpoints within intron 7 of EEF1G and intron 20 of ALK . As the fusions were identified by RNA-Seq, genetic mechanisms underlying these rearrangements are unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Even though the complete PTK domain is involved, the ALK fragment contains the final 513 amino acids, which is shorter in comparison to the fragment involved in most other ALK fusions, containing the final 563 amino acids. 42 Of note, both cases reported by Palacios et al 33 revealed breakpoints within intron 7 of EEF1G and intron 20 of ALK . As the fusions were identified by RNA-Seq, genetic mechanisms underlying these rearrangements are unknown.…”
Section: Discussionmentioning
confidence: 91%